Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae). VII. The cornigera species group, with descriptions of six new species - Wang, Shuxia; Liu, Chen (Zootaxa, 2020)
The cornigera species group of the genus Promalactis Meyrick, 1908 is proposed based on the forewing patterns. Species of this group are characterized by the forewing with the costal and ventral areas densely covered with dark scales forming ill-defined dark bands along the basal 2/5 to 3/4, respectively, and the dorsum with two pale parallel streaks. Six new species are described: P. albipectinalis sp. nov., P. flavidilineata sp. nov., P. grandaedeaga sp. nov., P. malipoensis sp. nov. and P. voluta sp. nov are from China, and P. latignatha sp. nov. is from Thailand. Photographs of adults and genitalia of the new species are provided.